Is supine percutaneous nephrolithotomy an alternative to prone percutaneous nephrolithotomy? Our experience at a tertiary care center - Nekkanti Rahul; Sandeep Kumar Reddy; Ifrah Ahmad Qazi; Vedamurthy Reddy Pogula; Venkatesh Velivela; Kashinath V Thakre (Asian Journal of Medical Sciences, 2022)
Background: Majority of urologists prefer the usual prone position for percutaneous nephrolithotomy (PCNL) but due to various disadvantages of prone PCNL, several alternative positions are being used. Aims and Objectives: The aim of the study was to compare the surgical outcomes of PCNL performed using supine position with those performed in the prone position. Materials and Methods: This was a prospective and observational study. After applying inclusion criteria, 60 renal calculi patients were randomly assigned to two groups, each with 30 patients, all demographic, operative, and post-operative characteristics were recorded. Results: Out of 60 patients, 38 (63%) patients were male and 22 (37%) were female. The mean age (in years) in prone PCNL was 45.03±17 while in supine, it was 51.7±15. Forty patients had mild, 12 had moderate, and eight had gross hydronephrosis. Stone size (mm) ranged from 20 to 55 with a mean stone size of 22.5±8.8 in prone PCNL and 23.9±13.5 in supine PCNL. The mean operative time (minutes) was 65.1±27.2 in prone PCNL and 68.7±16 in supine PCNL (P=0.068). Complete stone clearance was seen in 26 (86%) patients in prone PCNL versus 25 (83%) patients in supine PCNL. Five patients in supine PCNL had Grade 1–2 complications. There were no serious complications in either group. The mean post-operative hospital stay (days) was 3.53 in prone PCNL versus 3.63 in supine PCNL, (P=0.715). Conclusion: Supine PCNL is an effective and safe procedure with similar operative time, stone-free rate, and complications to prone PCNL.